CORONARY ARTERY DISEASE IN PATIENTS OF PERIPHERAL ARTERIAL DISEASE: AN OBSERVATIONAL STUDY - SHAHZAD, MMK; JAFFRI , SKA; GHOUS, MW (Biological and Clinical Sciences Research Journal, 2024)
Peripheral arterial disease (PAD) and coronary artery disease (CAD) share common risk factors and pathophysiological mechanisms. However, the frequency and co-occurrence of CAD in patients diagnosed with PAD remain underexplored in clinical practice. Understanding this relationship is vital for improving diagnostic strategies and patient outcomes. Objectives: To determine the frequency of coronary artery disease (CAD) in patients diagnosed with peripheral arterial disease (PAD). Methods: This study was conducted in the department of cardiology after approval from the hospital’s ethical committee, between January and June 2024. A detailed history and physical examination were performed on 160 individuals who met the inclusion criteria. Clinical data, including demographics, risk factors (hypertension, diabetes, smoking, dyslipidemia, family history of CAD), symptoms of PAD, and Ankle-Brachial Index (ABI) measurements, were collected. CAD screening was done using ECG, echocardiography, and coronary angiography or CTA for high-risk patients. Significant CAD was defined as ≥70% narrowing in major epicardial arteries or ≥50% in the left main coronary artery. PAD was confirmed through imaging studies and was severe enough to require referral for vascular surgery. A predesigned questionnaire was used for data collection, and SPSS Version 26 was utilized for statistical analysis. Results: The mean age of the enrolled patients was 45.97±8.78 years. The study included 160 individuals, with 51.3% (n=82) males and 48.8% (n=78) females. Age distribution showed that 0.5% (n=8) were 18-30 years old, 10.6% (n=17) were 31-40 years old, 55.0% (n=88) were 41-50 years old, and 29.4% (n=47) were over 50 years old. Regarding coronary artery disease (CAD), 44.4% (n=71) of participants were diagnosed with CAD. Among males, 52.4% (n=43) had CAD compared to 35.9% (n=28) of females, showing a statistically significant difference (p=0.03). In terms of age groups, 45.2% (n=14) of individuals aged 18-30 years, 32.0% (n=8) of those aged 31-40 years, 45.8% (n=27) of those aged 41-50 years, and 48.9% (n=22) of those over 50 years had CAD, but the association between CAD and age was not statistically significant (p=0.57). Conclusion: The study concluded that there is a high frequency of coronary artery disease (CAD) in patients with peripheral arterial disease (PAD), emphasizing the importance of early detection, thorough cardiovascular evaluation, and a multidisciplinary approach to enhance patient outcomes.